2013
DOI: 10.1155/2013/607939
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens as Antioxidant Modulators in Human Fertility

Abstract: Among treatments proposed for idiopathic male infertility, antiestrogens, like tamoxifen, play a possible role. On the other hand, oxidative stress is a mechanism well recognized for deleterious effects on spermatozoa function. After reviewing the literature on the effects of estrogens in modulation of antioxidant systems, in both sexes, and in different in vivo and in vitro models, we suggest, also on the basis of personal data, that a tamoxifen treatment could be active via an increase in seminal antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…NF-kB) activated by oxidative stress (Nandakumar et al 2008;Morgan & Liu 2011). Based upon a variety of studies, it appears that female hosts tend to have stronger anti-oxidant defense responses than their male counterparts (Borras et al 2003;Badeau et al 2005;Vina et al 2011;Mancini et al 2013). For example, it has been reported that mitochondria from Wistar rats of control females produced only half of the levels of peroxides compared with males and ovariectomized females (Borras et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB) activated by oxidative stress (Nandakumar et al 2008;Morgan & Liu 2011). Based upon a variety of studies, it appears that female hosts tend to have stronger anti-oxidant defense responses than their male counterparts (Borras et al 2003;Badeau et al 2005;Vina et al 2011;Mancini et al 2013). For example, it has been reported that mitochondria from Wistar rats of control females produced only half of the levels of peroxides compared with males and ovariectomized females (Borras et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the general beliefs stress can be defined also at cellular level as an oxidative stimulus. Oxidative stress (OS) is an unbalance between production of free radicals, molecules characterized by high reactivity (like reactive oxygen species (ROS) such as superoxide anion, hydrogen peroxide, and the hydroxyl radical) and antioxidant (such as glutathione, vitamins, catalase, superoxide dismutase, and various peroxidases) defenses in biological systems ( Figure 3 ) [ 16 ]. Enhancement in ROS and their metabolites can attack the cell membrane, and they can result in modification of the DNA, lipids, and proteins (such as tyrosine nitration and S-glutathionylation), altering enzymatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in leukocytes and many other cells (endothelial cells, mesangial cells, fibroblasts, thyrocytes, oocytes, Leydig cells, adipocytes, etc.) ROS generation has been assessed to have a positive physiological role protecting the cells from pathological stimuli [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total antioxidant capacity (TAC) expresses the whole effects of nonproteic nonenzymatic antioxidants, as widely discussed in previous studies [21,22]. Previously, we have shown the modulatory action of anabolic hormones on this parameter and its variations in CHF [20,23].…”
Section: Introductionmentioning
confidence: 99%